A study to assess the applicability of the communicative approach in the teaching and learning of English Language at Ordinary Level - Mangisi, Jannet (Midlands State University, 2019)
The study sought to assess the applicability of the Communicative Approach in the teaching of English Language at Ordinary Level in order to establish the extent to which the approach is being implemented by Ordinary Level English Language teachers. The study was conducted in the Lalapanzi Cluster of Chirumanzu District in the Midlands Province. The problem is that despite the introduction of Communicative Language Teaching, many teachers are employing structural methods to language teaching. The literature review done showed that the CLT view of language is functional and interactional while the goal of language teaching is communicative competence. The literature review also revealed that CLT is a learner – centred approach which requires collaboration and use of task based activities for learners to achieve communicative competence. In this study, 4 secondary schools, 40 Ordinary Level English Language learners as well as 5 Ordinary Level English Language teachers were involved. Purposive sampling was used to select the four schools; simple random selection was used to select the learners in the sample. The researcher included all the 5 English Language teachers in the sample. Questionnaires were administered to gather information from both teachers and learners. Document analysis was also used to gather data. Data gathered were quantitatively and qualitatively analysed and presented in the form of tables, graphs, pie charts, descriptions and paraphrases. The study established that besides the recommendation by the Zimbabwe Schools Examination Council (ZIMSEC) for the use of Communicative Language Teaching, English Language teachers use traditional structural approaches in their profession. Such adherence to traditionalism has been shown to be a result of lack of CLT conceptualization on the part of the teachers. The research recommends the Ministry of Primary and Secondary Education, influential institutions such as colleges and universities as well as textbook writers to spearhead English Language policies and techniques that will effect the application of Communicative Language Teaching in the teaching and learning of English Language